Cerebral angiogenesis ameliorates pathological disorders in Nemo-deficient mice with small-vessel disease. Issue 2 (February 2021) - Jiang, Yun; Müller, Kristin; Khan, Mahtab A.; Assmann, Julian C.; Lampe, Josephine; Kilau, Knut; Richter, Marius; Kleint, Maximilian; Ridder, Dirk A; Hübner, Norbert; Schmidt-Supprian, Marc; Wenzel, Jan; et al.
Cerebral small-vessel diseases (SVDs) often follow a progressive course. Little is known about the function of angiogenesis, which potentially induces regression of SVDs. Here, we investigated angiogenesis in a mouse model of incontinentia pigmenti (IP), a genetic disease comprising features of SVD. IP is caused by inactivating mutations of Nemo, the essential component of NF-κB signaling. When deleting Nemo in the majority of brain endothelial cells ( Nemo beKO mice), the transcriptional profile of vessels indicated cell proliferation. Brain endothelial cells expressed Ki67 and showed signs of DNA synthesis. In addition to cell proliferation, we observed sprouting and intussusceptive angiogenesis in Nemo beKO mice. Angiogenesis occurred in all segments of the vasculature and in proximity to vessel rarefaction and tissue hypoxia. Apparently, NEMO was required for productive angiogenesis because endothelial cells that had escaped Nemo inactivation showed a higher proliferation rate than Nemo -deficient cells. Therefore, newborn endothelial cells were particularly vulnerable to ongoing recombination. When we interfered with productive angiogenesis by inducing ongoing ablation of Nemo, mice did not recover from IP manifestations but rather showed severe functional deficits. In summary, the data demonstrate that angiogenesis is present in this model of SVD and suggest that it may counterbalance the loss of vessels.